2023
DOI: 10.3390/microorganisms11061432
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Multi-Drug Resistant Pseudomonas aeruginosa Sequence Type 235 Isolated from Sudan

Mohamed A. Hussain,
Malik Suliman Mohamed,
Hisham N. Altayb
et al.

Abstract: Pseudomonas aeruginosa (P. aeruginosa) is known to be associated with resistance to practically all known antibiotics. This is a cross-sectional, descriptive, laboratory-based analytical study in which 200 P. aeruginosa clinical isolates were involved. The DNA of the most resistant isolate was extracted and its whole genome was sequenced, assembled, annotated, and announced, strain typing was ascribed, and it was subjected to comparative genomic analysis with two susceptible strains. The rate of resistance was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…on cerebrospinal fluid; 36.6% of the isolates were MDR of which 69.2% were Gram-negatives and 30.8% were Gram-positives [ 20 ]. Additionally, in Sudan, 80% of K. pneumoniae were reported as MDR [ 21 ], and one more study found that there was a high prevalence of MDR Enterobacteriaceae ; mainly ESBL-positive E. coli and K. pneumoniae [ 22 ], Whereas 18% of P. aeruginosa isolates were MDR in a recent work published in 2023 [ 23 ], and 89.2% of S. aureus were MDR, of them 67.6% were methicillin resistant [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…on cerebrospinal fluid; 36.6% of the isolates were MDR of which 69.2% were Gram-negatives and 30.8% were Gram-positives [ 20 ]. Additionally, in Sudan, 80% of K. pneumoniae were reported as MDR [ 21 ], and one more study found that there was a high prevalence of MDR Enterobacteriaceae ; mainly ESBL-positive E. coli and K. pneumoniae [ 22 ], Whereas 18% of P. aeruginosa isolates were MDR in a recent work published in 2023 [ 23 ], and 89.2% of S. aureus were MDR, of them 67.6% were methicillin resistant [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%